Low Soil Nutrient Tolerance and Mineral Fertilizer Response in White Guinea Yam (Dioscorea rotundata) Genotypes - Matsumoto, Ryo; Ishikawa, Haruki; Asfaw, Asrat; Asiedu, Robert (Frontiers in Plant Science, 2021)
Yam (Dioscorea spp.) is a major food security crop for millions of resource-poor farmers, particularly in West Africa. Soil mineral deficiency is the main challenge in yam production, especially with the dwindling of fallow lands for the indigenous nutrient supply. Cultivars tolerant to available low soil nutrients and responsive to added nutrient supply are viable components of an integrated soil fertility management strategy for sustainable and productive yam farming systems in West Africa. This study's objective was to identify white Guinea yam (D. rotundata) genotypes adapted to available low soil nutrients and responsive to externally added nutrient supply. Twenty advanced breeding genotypes and a local variety (Amula) were evaluated under contrasting soil fertility, low to expose the crop to low fertility stress or available low soil nutrient supply and high to assess the crop response to added mineral fertilizer (NPK) input at Ibadan, Nigeria. The genotypes expressed differential yield response to low soil fertility (LF) stress and added fertilizer input. Soil fertility susceptibility index (SFSI) ranged from 0.64 to 1.34 for tuber yield and 0.60 to 1.30 for shoot dry weight. The genotypes R034, R041, R050, R052, R060, R100, and R125 combined lower SFSI with a low rate of reduction in tuber yield were identified as tolerant to LF stress related to the soil mineral deficiency. Likewise, the genotypes R109, R119, and R131 showed high susceptibility to soil fertility level and/or fertilizer response. Genotypes R025 and R034 had the tuber yielding potential twice of that the local variety under low soil nutrient conditions. Shoot dry weight and tuber yield showed a positive correlation both under low and high soil fertility conditions (r=0.69 and 0.75, respectively), indicating the vigor biomass may be a morphological marker for selecting genotypes of white Guinea yam for higher tuber yield. Our results highlight genotypic variation in the tolerance to low soil nutrients and mineral fertilizer response in white Guinea yam to exploit through breeding and genetic studies to develop improved genotypes for low and high input production systems in West Africa.